Perspectives of teachers’ on the selection and the development of the school leaders in the United Arab Emirates - Arulraj David, Solomon (2019)
Purpose– The purpose of this paper is to examine teachers’ perspectives on school leaders’ selection and development strategies in order to propose/recommend strategies that are relevant to the context of the United Arab Emirates. Design/methodology/approach– The study gathered data through group discussion of school teachers who attended the module “leadership for school improvement” taught by the researchers. The teachers who participated in this study include local and expat teachers who are currently working in both public and private schools in the UAE. The reports of the group discussion were used as transcripts and thematic analysis was used to analyse the results. Findings– The results indicate that there is a strong aspiration for setting better standards for the selection of the school leaders. There is great interest in engaging experts and instrumenting accredited continued professional development training on developing school leaders. The respondents emphasised on the required qualifications, experiences and knowledge, and the need for mentorship approach. Research limitations/implications– The key limitation of the study is the smaller sample size. Practical implications– The outcome of the study offers necessary insight to the decision makers on the selection and development of school leaders in the UAE. Social implications– The study insists that the social and cultural values of the UAE to be considered in the selection and development of school leaders in the UAE. Originality/value– The study offers potential gap and scope for further research on school leadership in the UAE that could be further explored with many samples and cases for broader understanding. Keywords United Arab Emirates, Leadership, Professional training, Development of school leaders, Selection of school leaders, Teachers’ perspectives Paper type Research paper.